Abundance of Mosquito Larvae at Jagannath University and Dhaka University Campus of Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2021)
A year-round survey on the abundance of mosquito larvae was conducted at Jagannath University - and Dhaka University - Campus from October 2018 to September 2019. A number of total 4415 mosquito larvae were collected of which 3086 were identified as Culex and 1329 were Aedes. Only 3 species belonging to 2 genera were identified in this study. At Jagannath University campus, highest number of Culex larvae was recorded in the month of August which was 167 (10.9%) and the lowest number was recorded in February which was 66 (4.3%), on the other hand, highest number of Aedes larvae was recorded in the month of July which was 137 (23.8%) and the lowest number was found in December which was 9 (1.6%). At Dhaka University campus, the highest number of Culex larvae was found in the month of April, which was 179 (11.5%) and the lowest number was found in June, which was 66 (4.3%), on the other hand, the highest number of Aedes larvae was found in the month of June which was 200 (26.5%) and lowest number was found in February which was 8 (1.06%). This study could be helpful in launching larvicidal programs in a more cost-effective way at these two urban public universities of Dhaka city.Bangladesh J. Zool. 49 (2): 321-329, 2021